Community Ecological Behavior in Preserving Coastal Areas (Case Study of Mallusetasi Sub-District) - Nugroho, Cahyadi; Umar, Ramli; ., Mithen (KnE Social Sciences, 2024)
This article describes the forms of ecological behavior found in the coastal areas of Barru Regency. The ecological behavior in question includes individual and community behavior in preserving the environment. The study was revealed through qualitative methods. Data were collected through observation, interviews, and documentation. The data analysis used is a qualitative analysis model. The results showed that at the individual level, a person’s ecological behavior toward the environment of the coastal area he lives in tends to be indifferent, such as the habit of throwing garbage in the river and the sea becomes commonplace. The river channel is often used as a dumping ground and individuals who live near the beach tend to throw their household waste directly into the sea. Individual awareness of environmental conservation is low, making it difficult to change habits that have been made. At the community level, awareness of ecological behavior will be formed when there are external stimuli such as government intervention and disaster events in the area. Individuals will tend to work together to clean up their environment when there are government intervention and the impact of disasters such as floods. From this research, it was found that individual awareness in ecological behavior is the main key in preserving the environment. On the other hand, support from the government or other cooperative institutions can also increase the tendency of people to behave ecologically. Keywords: behavior, coastal area, environment, ecology, community